Accuracy of the 4-Stage Balance Test and Sensor-Based Trunk Sway as Fall Risk Assessment Tools in the Emergency Department. Issue 2 (April 2021) - Southerland, L. T.; Kloos, A. D.; Slattery, L.; Tan, Y.; Young, G.; Rosenthal, J.; Kegelmeyer, D. A.
Abstract : Purpose: Falls are the leading cause of injury-related emergency department (ED) visits in older adults, but we lack a sensitive screening tool for fall risk. We evaluated the sensitivity and specificity of the 4-Stage Balance Test (4SBT) to identify older adults at risk of falling in an ED setting and whether accelerometry-based trunk sway measures could improve identification. Methods: Participants were 63 ambulatory adults 65 years and older in the ED, of which 47% reported a fall in the past year. Outcome measures were the 4SBT and trunk sway. Participants identified as being at risk of falling received recommendations for follow-up care. Participants were contacted 8 ± 2 weeks after their ED visits to assess compliance with ED recommendations. Results: No strong association was found between reported falls and completion of the first 3 positions of the 4SBT ( P = .063). The best model was staggered stance plus average anterior-posterior sway and posterior sway of the thorax ( P = .004, area under receiver operating curve = 0.8). On follow-up, 21% of those identified as being at risk, and available for follow-up, had fallen; 2 reported multiple falls. Conclusions: Administration of the first 2 positions of the 4SBT combined with measurement of posterior sway is a quick method for fall risk assessment in the ED.